Socio-cultural determinants of on-farm policies and innovation adoption in Ghana - Ofosu-Ampong, Kingsley; Yaovi Comlan, Rene; Jizorkuwie, Abdul-latif Baamonyor; Yeboah, Patricia Amankwaa; Masoud, Jalaludeen; Abera, Wuletawu (IISTE, 2025)
This study investigates the influence of socio-cultural factors such as social network ties, traditional knowledge and farmer incentives on-farm policies and innovation adoption in Upper West Region of Ghana. Using a cross sectional design, we collected data from 568 farmers who cultivate cereals and legumes such as maize, millet, sorghum, soybeans and groundnuts. The results show that while formal rituals are rare, farmers widely incorporate traditional knowledge into their decision-making process, suggesting the value of practical traditional wisdom. The findings also suggest that investment in both demonstration programs and longitudinal research could significantly increase innovation adoption rates, particularly when results are communicated in ways that build trust among more skeptical agricultural stakeholders. The hierarchical regression analysis results show that the adoption of on-farm policies and innovations is primarily shaped by farmers’ attitudes and beliefs, supported by the strength of their social networks, and reinforced by incentives and risk-buffering mechanisms. Attitudes and beliefs emerged as the strongest predictor, highlighting the centrality of farmers’ personal convictions in adoption decisions. This study contributes by highlighting the need for policy and program design to prioritize interventions that build farmers’ confidence in innovations while leveraging community-based networks to enhance dissemination. This calls that scaling adoption requires long-term demonstration and communication strategies that build trust across diverse farming contexts. Awareness campaigns, participatory demonstrations, and farmer-to-farmer exchanges are particularly effective in shifting attitudes. By prioritizing confidence-building measures, policies can strengthen positive attitudes, which then allow incentives and social networks to more effectively enhance adoption.